2017
DOI: 10.1111/1365-2745.12751
|View full text |Cite
|
Sign up to set email alerts
|

Transmission and temporal dynamics of anther‐smut disease (Microbotryum) on alpine carnation (Dianthus pavonius)

Abstract: Summary Theory has shown that sterilizing diseases with frequency‐dependent transmission (characteristics shared by many sexually transmitted diseases) can drive host populations to extinction. Anther‐smut disease (caused by Microbotryum sp.) has become a model plant pathogen system for studying the dynamics of vector‐ and sexually transmitted diseases: infected individuals are sterilized, producing spores instead of pollen, and the disease is spread between reproductive individuals by insect pollinators. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
112
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 49 publications
(113 citation statements)
references
References 57 publications
1
112
0
Order By: Relevance
“…Vector transmission is typically frequency‐dependent (Antonovics, Iwasa, & Hassell, ; McCallum, Barlow, & Hone, ), so disease establishment and persistence should not depend on a threshold host density (Getz & Pickering, ; Lloyd‐Smith et al., ). Detailed marked‐plant studies of the transmission within a single large population of D. pavonius in the range centre have shown that transmission is actually a mixture of frequency‐dependent pollinator‐transmission and density‐dependent wind transmission (Bruns et al., ). However, theoretical models of mixed frequency and density‐dependent transmission have shown that even small levels of frequency‐dependent transmission increase the conditions for disease persistence and reduce the threshold density for disease invasion (Ryder, Miller, White, Knell, & Boots, ).…”
Section: Discussionmentioning
confidence: 99%
“…Vector transmission is typically frequency‐dependent (Antonovics, Iwasa, & Hassell, ; McCallum, Barlow, & Hone, ), so disease establishment and persistence should not depend on a threshold host density (Getz & Pickering, ; Lloyd‐Smith et al., ). Detailed marked‐plant studies of the transmission within a single large population of D. pavonius in the range centre have shown that transmission is actually a mixture of frequency‐dependent pollinator‐transmission and density‐dependent wind transmission (Bruns et al., ). However, theoretical models of mixed frequency and density‐dependent transmission have shown that even small levels of frequency‐dependent transmission increase the conditions for disease persistence and reduce the threshold density for disease invasion (Ryder, Miller, White, Knell, & Boots, ).…”
Section: Discussionmentioning
confidence: 99%
“…Overall disease prevalence in this area has been close to 40% for the entire time (Bruns et al. ), but there is significant heterogeneity in host and pathogen density at a more fine‐scale local level (J. Antonovics et al., unpubl. data).…”
Section: Methodsmentioning
confidence: 98%
“…In D. pavonius , the disease is systemic, affecting all flowers on the plant, and recovery is extremely rare (Bruns et al. ). Pollinators are the main route for spore dispersal, although localized aerial dispersal also occurs (Bruns et al.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations